IMPACT OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN TEACHING-LEARNING PROCESS - Rivera Muñoz, Jorge Leoncio (2014)
In the past decade is frequent use of information and communication technologies as part of the educational and pedagogical task, since it develops a variety of relationships, behaviors, attitudes, roles, skills and other domains, which involves creativity and innovation based on the capabilities and interest of those involved so it has become an essential tool for teaching and learning processes, information, communication, and the generation, appropriation and use of knowledge and the development of technology, science and knowledge, requiring only the use of Internet, telematics, robotics, computer, technology, cyber, cyberspace, cyber art and the like, with very specific performance criteria that would help address the how and with what care the nature of learning and performance of teachers.